Sex Differences in Metabolic and Behavioral Responses to Exercise but Not Exogenous Osteocalcin Treatment in Mice Fed a High Fat Diet - Winberg, Jordan; Rentz, Jesse; Sugamori, Kim; Swardfager, Walter; Mitchell, Jane (Frontiers in Physiology, 2022)
Background: Exercise helps improve glucose handling in diabetes and has been shown to improve mood and cognition in other conditions. Osteocalcin, a protein produced by bone osteoblasts, was reported to have endocrine actions to improve both metabolism and also improve age-related cognitive deficits in mice. Methods: This study was designed to compare the effects of daily treadmill running exercise with injection of osteocalcin in high fat diet (HFD) induced diabetes in male and female C57BL/6J mice. Following established glucose intolerance and treatment for eight weeks, mice were assessed for anxiety on an elevated plus maze, motivation by tail suspension test and cognition and memory in a puzzle box. Endogenous osteocalcin was measured by ELISA. Results: Mice on HFD had high weight gain, glucose intolerance and increased white fat. Exercise increased circulating osteocalcin levels in female mice but decreased them in male mice. Exercise also decreased weight gain and improved glucose tolerance in female but not male mice; however, treatment with osteocalcin made no metabolic improvements in either males or females. HFD induced anxiety only in female mice and this was not improved by osteocalcin. Exercise induced anxiety only in male mice. HFD also increased depressive-like behaviour in both sexes and this was improved by either exercise or osteocalcin treatment. Cognitive deficits were seen in both male and female mice on HFD. Exercise improved cognitive performance in female but not male mice, while osteocalcin treatment improved cognitive performance in both sexes. Conclusions: There were sex differences in the effects of exercise on endogenous osteocalcin regulation that correlated with improvements in cognitive but not metabolic outcomes. Exogenous osteocalcin did not improve metabolism but was effective in improving HFD-induced cognitive deficits. Sex is an important variable in hormonal and cognitive responses to exercise in diabetes.